Konstruksi Realitas dalam Infotainment Silet - Siti Mariyam (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2016)
This paper aims to analyze the discourse of motto used by Silet, the most favorite infotainment programs of Panasonic Gobel Awards. The research found that Silet has used language that can transform reality. Using language, Silet has constructed meaning to audiences that information presented has changed from original form. Something that is taboo now can be worthy to discuss it after broadcasted by Silet. Silet gives suggestion and ‘false consciousness’ to audiences that everything presented by Silet is good and right. The use of words and motto is a tactic to make proper banality of news content presented by Silet.